Hubungan Durasi Screen Time terhadap Kualitas Tidur Remaja di Jawa Barat Selama Masa Pandemi COVID-19 - Andika Aulia Ramadhan; Titik Respati; Raden Ganang Ibnusantosa (Bandung Conference Series: Medical Science, 2022)
Abstract. In adolescents, poor sleep quality, especially in the final period, is frequent. The Covid-19 pandemic exaggerated the problem with restrictions on social interactions affecting the application of home learning makes adolescent screen time increase to affect sleep quality. The purpose of this study was to analyze the relationship of increasing screen time duration in adolescents undergoing online learning in West Java during the pandemic in the period 2020 - 2021. This study uses observational analytical methods with quantitative cross-sectional designs. Data collection runs from October to November 2021 through social media. The data taken is primary data using the Pittsburgh Sleep Quality Index (PSQI) questionnaire. The number of samples in this study was 223 people. The results of the univariate statistical test showed showed students with screen time >2 hours as many as 46 people (20.63%) with poor sleep quality and 152 people (68.16%) with moderate sleep quality. The results of the bivariate analysis showed there is no association between screen time duration during online learning and sleep quality (p=1.000). The conclusion in this study is that there is no relationship between screen time duration in adolescents undergoing online learning with sleep quality in West Java during the pandemic in the period 2020 – 2021. Abstrak. Kualitas tidur yang buruk pada remaja khususnya periode akhir masih menjadi permasalahan yang sering terjadi, ditambah dengan adanya pandemi Covid-19 yang mengharuskan penerapan belajar di rumah membuat waktu screen time remaja bertambah sehingga dapat mempengaruhi kualitas tidur. Tujuan penelitian ini untuk menganalisis hubungan durasi screen time pada remaja yang menjalani pembelajaran daring di Jawa Barat selama pandemi berlangsung pada periode 2020 – 2021. Penelitian menggunakan metode analitik observasional dengan desain cross sectional secara kuantitatif. Pengumpulan data dimulai dari Oktober hingga November 2021 melalui sosial media. Data yang diambil merupakan data primer dengan menggunakan kuisioner Pittsburgh Sleep Quality Index (PSQI). Jumlah sampel pada penelitian ini sebanyak 223 orang. Hasil uji statistik univariat didapatkan karakteristik Mahasiswa dengan screen time >2 jam sebanyak 46 orang (20,63%) dengan kualitas tidur buruk dan 152 orang (68,16%) dengan kualitas tidur sedang. Hasil analisis bivariat didapatkan tidak terdapat hubungan antara durasi screen time selama pembelajaran daring dengan kualitas tidur (p=1.000). Kesimpulan pada penelitian tidak terdapat antara durasi screen time selama pembelajaran daring dengan kualitas tidur remaja di Jawa Barat pada periode 2020 – 2021.